Thiolutin Derivatives as inhibitor of RNA-Dependent RNA Polymerase (RdRP) of Hepatitis C Virus: An In-silico Approach - Muhammad Imran Qadir; Asma Munawar; Syed Bilal Hussain (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2018)
Docking study of few Thiolutin derivatives, which originally act as Hepatitis C Virus RNA Dependent RNA Polymerase (RdRP) inhibitor, was performed by using AutoDock Vina. The docking studies reveal that thiolutin interacted with Hepatitis C Virus RNA Dependent RNA Polymerase through hydrogen bonding as well as hydrophobic interactions. Its binding energy after modification (Thiolutin1) was -6.7 kcal/mol, which was greater than the original thiolutin affinity.